2022
DOI: 10.23918/ijsses.v9i2p141
|View full text |Cite
|
Sign up to set email alerts
|

Does PBL – Project-Based Learning Expert Visit Facilitate the PBL Implementation Process in Undergraduate EFL Classes?

Abstract: In this era of globalization, which is marked by the usage of the Internet, English as the world's first language plays an important role in almost all spheres. It undoubtedly sets up new demands for English language acquisition (English teaching and learning), and for more professional, 21 st -century related English. This paper attempts to investigate whether the undergraduate EFL learners, PBL expert and PBL implemented school visits, before implementing PBL (Project-Based Learning), have a positive effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…This could be achieved by assessing both disciplinary content knowledge and language in students' projects, which should be announced to students before commencing their projects. Teachers' professional development seems to be a critical issue in implementing PBL (Sartika et al, 2022), and having experts in the disciplines and in the PBL approach, as suggested by (Kavlu, 2022), could be considered to develop EFL teachers' competence in applying PBL in their classes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This could be achieved by assessing both disciplinary content knowledge and language in students' projects, which should be announced to students before commencing their projects. Teachers' professional development seems to be a critical issue in implementing PBL (Sartika et al, 2022), and having experts in the disciplines and in the PBL approach, as suggested by (Kavlu, 2022), could be considered to develop EFL teachers' competence in applying PBL in their classes.…”
Section: Discussionmentioning
confidence: 99%
“…The lecturer encouraged the students to visit companies, shops, and other places to observe and gain experience through discussions with experienced people in related fields, particularly by seeking advice on starting a new business and succeeding. As T. T. H. Nguyen and Pham (2016) noted, ESP teachers may lack specialized knowledge, and the lecturer in this course filled that gap by exposing students to authentic business contexts and field experts (Kavlu, 2022). As suggested by the lecturer, the second and third weeks-information gathering and processing-were devoted to discussions on the information they had gathered for their projects and drafting their projects for presentations.…”
Section: The Implementation Of Pbl In An English For Business Coursementioning
confidence: 99%
See 1 more Smart Citation
“…Students are accommodated to be creative in producing relevant products from learning materials and content. Through the creation of these ideas, students are expected to be able to translate learning content independently, so that learning outcomes can be obtained optimally (Kavlu, 2022;Livet et al, 2023).…”
Section: Introductionmentioning
confidence: 99%